Modeling of the co-pyrolysis of rubber residual and HDPE waste using the distributed activation energy model (DAEM) - Ng, Q.H. (Elsevier Ltd, 2018)
The kinetic analysis for rubber residual i.e. rubber seed shell, high density polyethylene (HDPE) waste and its mixture are investigated using distributed activation energy model (DAEM) reaction model. Furthermore, the pyrolysis characteristics from these materials are investigated by non-isothermal thermogravimetric analysis from temperature 323 K to 1173 K at varying heating rates range of 10â200 K/min in inert argon atmosphere. The average value determined for activation energy, Ea and pre-exponential factor, k0 are 54.888 kJ molâ1 and 6.923 Ã 104 sâ1 respectively for RSS, 75.396 kJ molâ1 and 1.346 Ã 106 sâ1 respectively for HDPE and 64.010 kJ molâ1 and 8.444 Ã 104 sâ1 respectively for binary mixture of RSS/HDPE. By taking these values as the initial guess for Gaussian distribution, and assuming the standard deviation, Ï is at 15 kJ molâ1, as well as constant k0 value for all first order reactions, the mean activation energy, E0 determined from the distribution curve for RSS, HDPE and RSS/HDPE are 55.0 kJ molâ1, 75.5 kJ molâ1 and 64.0 kJ molâ1 respectively. The values of E0 and k0 in pyrolysis of binary mixture of RSS/HDPE are found to be lower compared to the individual component of RSS and HDPE in pyrolysis process. Â© 2018 Elsevier Ltd